Baseline characteristics of children with juvenile dermatomyositis enrolled in the first year of the new Childhood Arthritis and Rheumatology Research Alliance registry - Jessica Neely; Kaveh Ardalan; Adam Huber; Susan Kim; for the Childhood Arthritis and Rheumatology Research Alliance Investigators (BMC, 2022)
Abstract Background To report baseline characteristics, patient reported outcomes and treatment of children with Juvenile Dermatomyositis (JDM) in the Childhood Arthritis and Rheumatology Research Alliance (CARRA) Registry. Methods Children newly diagnosed with JDM were enrolled in the CARRA Registry from 41 pediatric rheumatology centers. Baseline patient demographics, disease characteristics, assessments, patient reported outcome and treatments were recorded. Results In the first year, 119 JDM participants were enrolled. Most were female (63.4%), and white (72.3%) with a median diagnosis age 8.0 years (IQR 4.0-11.5), and median age of disease onset 7.0 years (IQR 3.5-7.5). They had characteristic rashes (92.4%), elevated muscle enzymes (83.2%), physician global score 4.0 (IQR 2.5-5.0) and manual muscle testing score 63.5 (IQR 51.0-75.0). Calcinosis (3.4%) and interstitial lung disease (< 1%) were uncommon. Myositis specific antibodies were measured and reported in nearly half of participants enrolled where anti-MJ followed by Anti-p155/140 were most common (11/49 and 7/53 respectively). Childhood Health Assessment Questionnaire (CHAQ) results showed mild-moderate disability (median 0.750, IQR 0.030-1.875), as did patient/parent global assessments of disease activity (median 3, patient IQR: 1.75-5.25; parent IQR: 1-7). Patient Reported Outcomes Measurement Information System (PROMIS®) Pediatric Global Health 7 scores, Pain Interference, Physical Function scores for Mobility, and Upper Extremity Function were commonly worse than 95% of the general pediatric population. Conclusions In its inaugural year, 119 JDM patients were successfully enrolled in participapte in the New CARRA Registy. This registry will provide the necessary foundation to advance clinical research to improve outcomes using traditional measures and patient reported outcomes. With the CARRA biorepository, this infrastructure will enable future translational research. Together, these efforts may aid in future clinical trials, including comparative effectiveness trials.